1990
DOI: 10.1007/bf02554969
|View full text |Cite
|
Sign up to set email alerts
|

Resolution-enhanced fourier transform infrared spectroscopy study of the environment of phosphate ions in the early deposits of a solid phase of calcium-phosphate in bone and enamel, and their evolution with age. I: Investigations in thev 4 PO4 domain

Abstract: In order to investigate the possible existence in biological and poorly crystalline synthetic apatites of local atomic organizations different from that of apatite, resolution-enhanced, Fourier transform infrared spectroscopy studies were carried out on chicken bone, pig enamel, and poorly crystalline synthetic apatites containing carbonate and HPO4(2-) groups. The spectra obtained were compared to those of synthetic well crystallized apatites (stoichiometric hydroxyapatite, HPO4(2-)-containing apatite, type B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
221
1
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(243 citation statements)
references
References 31 publications
14
221
1
7
Order By: Relevance
“…The former of the newly appeared peak (1150-900 cm -1 ) was assignable to the stretching vibration (n 3 ) of the phosphate (PO 4 3-) groups and the latter (650-500 cm -1 ) represented the bending vibration (n 4 ) of the phosphate (PO 4 3-) groups [16]. In the case of standard HAp samples having stoichiometric chemical composition and relatively high crystallinity, both of these two peaks split into a number of distinct peaks (data not shown), same as the case that reported in literatures [16][17][18]. The broad shape of these peaks indicated that the obtained HAp deposits had low crystallinity or other crystal phase of calcium phosphates co-existed.…”
Section: Hap Deposition On Serum Protein-adsorbed Ps Surfacessupporting
confidence: 65%
“…The former of the newly appeared peak (1150-900 cm -1 ) was assignable to the stretching vibration (n 3 ) of the phosphate (PO 4 3-) groups and the latter (650-500 cm -1 ) represented the bending vibration (n 4 ) of the phosphate (PO 4 3-) groups [16]. In the case of standard HAp samples having stoichiometric chemical composition and relatively high crystallinity, both of these two peaks split into a number of distinct peaks (data not shown), same as the case that reported in literatures [16][17][18]. The broad shape of these peaks indicated that the obtained HAp deposits had low crystallinity or other crystal phase of calcium phosphates co-existed.…”
Section: Hap Deposition On Serum Protein-adsorbed Ps Surfacessupporting
confidence: 65%
“…In addition, the broad band centered between 550 and 560 cm -1 , assigned to acid phosphate (HPO 4 2-) in the mineral lattice, was much more intense in Mg doped HA nucleated on Collagen. These peculiarities of MgHA/Coll can be similarly observed in the FTIR spectrum of young bone; while they tend to disappear in mature bone and in highly crystalline synthetic apatite [28][29][30]. Correlation was noted between the fractional intensity of ~1050 cm -1 band related to PO 4 3-group and the crystal size of the apatite: a reduction of the apatitic crystal size induced an increase of the percentage area of this component [31,32].…”
Section: Development and Characterization Of The Lower (Bony) And Intmentioning
confidence: 53%
“…Another specificity of biological apatites, which was more recently established, is the presence of hydrogen phosphate (HPO 4 2´) ions in PO 4 3´s ites [21][22][23]. These two types of bivalent ions substituting for PO 4 3´( type B CO 3 2´a nd HPO 4 2´) have been shown to correspond to the formation of calcium deficient apatites, the chemical formulas of which have been the subject of several works, essentially based on the composition of model minerals proposed by mineralogists or synthetic analogues.…”
Section: Structure and Chemical Formulasmentioning
confidence: 99%
“…More recently, these models, which are based on well-crystallized apatites, were re-examined due to the discovery, using mostly spectroscopic techniques (Fourier transform infrared (FTIR), Raman and solid-state nuclear magnetic resonance (NMR) spectroscopies), of the existence of specific spectral lines in the spectra of biological nanocrystalline apatites which do not appear for well-crystallized apatites and which have been designated as "non-apatitic environments" of the mineral ions [22,23,27,28]. These "non-apatitic" phosphate and carbonate environments have been shown to appear more clearly in the ν 4 PO 4 and ν 2 CO 3 domains of FTIR spectra.…”
Section: Non-apatitic Environments and The Hydrated Layermentioning
confidence: 99%